A Study of Sarcasm of TV Series Friends - Ryo Tauhid Ramadhan; Winda Setiasari (TRANSFORM : Journal of English Language Teaching and Learning, 2022)
The objectives of this study were to find out 1) The types of sarcasm in TV Series Friends, and 2) The purpose of sarcasm in TV Series Friends. The data were analyzed in descriptive qualitative research. The data of this research were from the utterance of Friends’ cast or character. The data were taken from all the words, phrases, clauses, sentences in Friends transcript which available on the internet. The result of this research showed that 1) there were four types of sarcasm are used by Friends’ character, namely: like-prefixed sarcasm with a total number 9 utterances (21.4%), lexical sarcasm with a total number 11 utterances (26.2%), propositional sarcasm with total 16 utterances (38.1%), and illocutionary 6 utterances (14.3%). 2) There were five purposes of sarcasm are used by Friends’ character, namely: sophistication with a total number 19 utterances (45.2%), evaluation with a total number 5 utterances (11.9%), tool for politeness with a total 5 utterances (11.9%), the persuasive aspect with a total number 7 utterances (16.7%), retract ability with a total 1 utterance (2.4%) and group affiliation with a total number 5 utterances (11.9%).